2021
DOI: 10.3390/su131810422
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis between the Role of Local Communities in Regional Development inside Japanese and Russian UNESCO’s Biosphere Reserves: Case Studies of Mount Hakusan and Katunskiy Biosphere Reserves

Abstract: The United Nations Educational Scientific and Cultural Organization has designated the Man and Biosphere Program to foster a better relationship between the environment and people. The topic of this study is to elucidate the role of local communities in the regional development of Biosphere Reserves with a focus on management roles (top-down or participatory) and the motivational drivers of the people involved (ecocentric or anthropocentric). Based on qualitative interviews taken from the two case studies of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In contrast, Russian BRs have shown more active local engagement than their Japanese counterparts, where regulations by the local authorities are still dominant. The differences between such kinds of management may depend on the historical relationship between government and local communities, perceptions of nature protection, and attitudes towards the economic gain from nature [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Russian BRs have shown more active local engagement than their Japanese counterparts, where regulations by the local authorities are still dominant. The differences between such kinds of management may depend on the historical relationship between government and local communities, perceptions of nature protection, and attitudes towards the economic gain from nature [20].…”
Section: Discussionmentioning
confidence: 99%
“…Other countries have more "top-down" implementations for the management of BR and GPs, where local governments or authorities are managing and regulating the programme. The differences between such kinds of management may depend on the historical relationship between government and local communities, perceptions on nature protection, and attitudes towards the economic gain from nature [20].…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, beyond ecological product valorisation, BR management entities are fervently searching for how to equip community residents with specialised education and training. For instance, in Katunskiy BR, Russia, in conjunction with NGOs, a comprehensive community development support Community livelihoods in BRs based on the sustainable livelihoods framework for the 21st century (Natarajan et al, 2022) (Mammadova et al, 2021).…”
Section: Diversified Livelihood Development Avenuesmentioning
confidence: 99%
“…Some study found that the Geoparks had more community involvement than the BRs. This distinction can be linked to the Geopark's bottom-up strategy, which places an emphasis on involving the local population through the growth of tourism [Mammadova et al 2021, Mammadova et al 2022. Although community capability is essential for bottom-up management, there are obstacles to overcome.…”
Section: Introductionmentioning
confidence: 99%